Stories in motion: integrating project-based digital-literary-platforms and tri-n-pedagogy to foster narrative writing in primary education - Atik Jayanti Kurnia; Siti Rochmiyati (Jurnal Ilmiah Pendidikan Dasar, 2026)
Narrative writing in Indonesian primary education remains underdeveloped and insufficiently supported, constrained by limited access to culturally grounded digital resources and pedagogical models. This research develops a digital literary platform and instructional module that integrates Project-Based Learning (PjBL) with the Tri-N philosophy, an experiential framework inspired by Ki Hajar Dewantara’s educational thought. Mixed-methods data were collected through surveys, interviews, document analysis, writing assessments, and classroom observations with 58 students across three schools. Quantitative analysis (independent sample t-tests) revealed significant improvements in students’ narrative writing performance, while qualitative findings highlighted increased engagement, creativity, and agency. The platform’s multimodal features, including interactive texts, student-generated content, audio narratives, and automated feedback, facilitated differentiated learning and collaborative composition. By explicitly framing Stories in Motion as a novel pedagogical framework, this research emphasises both its technological design and its empirical impact. This contribution offers a replicable model that integrates local philosophy with responsive technology, strengthening literacy outcomes while positioning Indonesian classrooms within global debates on digital narrative pedagogy. Ultimately, Stories in Motion fosters narrative writing in primary education by bridging pedagogy and technology.